Implementation of Personnel Administration in Improving the Effectiveness of Human Resource Management in Elementary Schools - Munawaroh, Faridatul; Soleha, Mar'atus (Jurnal Pendidikan Nusantara, 2025)
This study aims to analyze the implementation of the administration of teacher and team member personnel at SDN 2 Sendang, which includes the process of recruitment, selection, placement, development, and administrative services as a strategic factor in increasing the effectiveness of human resource management in the educational environment. The research used a case study method with a qualitative descriptive approach through observation techniques for one month, interviews with principals and teachers for two days, and documentation to obtain empirical data on school personnel management practices. Data analysis is carried out through the stages of data reduction, data presentation, and conclusion drawn/verification by triangulating sources to ensure validity. The results of the study show that the recruitment of education personnel at SDN 2 Sendang is carried out through the stages of announcement, candidate search, selection, and signing of employment contracts. At the same time, team member placement refers to the compatibility of competencies with the tasks needed by the School. Personnel development is carried out through coaching, training, performance evaluation, and the provision of incentive-based compensation to increase work motivation. Personnel administration services that include inventory of school facilities, preparation of reports, and assignment arrangements play an important role in supporting the smooth operation of education. The research concludes that systematic and competency-based personnel administration is proven to increase productivity, job satisfaction, and quality of educational services, and needs to be supported by the use of technology and collaborative culture for the sustainability of improving school quality.